2015
DOI: 10.1007/s10528-015-9687-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polymorphisms in Disease Severity in β-Thalassemia

Abstract: β-Thalassemia is a genetic disorder with a continuum of mild to severe clinical manifestations and requirement of transfusion at different stages of life. The cause(s) of this variety is not clear but genetic alterations could be a potential factor. In this review, the correlation between polymorphisms and different clinical manifestations, including the need for transfusion, was investigated. Relevant articles published in pubmed database from 1982 onwards were studied and compiled. The articles all contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Our results agree with Sclafani et al (2013) who found that, the frequency of the GSTM1-null genotype range from 23 to 62% in different population around the world (Sclafani et al, 2013). However, Rabab et al (2013) reported that GSTM1 null genotype was 44% in Egyptian population; on the other hand, GSTM1 deletion polymorphism for African-Americans was found to be 23-35% and for Chileans was 21% (Rabab et al, 2013).…”
Section: Pcrsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results agree with Sclafani et al (2013) who found that, the frequency of the GSTM1-null genotype range from 23 to 62% in different population around the world (Sclafani et al, 2013). However, Rabab et al (2013) reported that GSTM1 null genotype was 44% in Egyptian population; on the other hand, GSTM1 deletion polymorphism for African-Americans was found to be 23-35% and for Chileans was 21% (Rabab et al, 2013).…”
Section: Pcrsupporting
confidence: 90%
“…Glutathione S-transferase (GST) enzymes belong to a super family of multifactorial isoenzymes that in addition of being well known detoxification agents are also involved in excretion processes of toxic molecules as well (Sclafani et al, 2013). Evidence suggests that the GST expression level is a crucial factor in determining cell sensitivity to a broad spectrum of toxic chemicals, as GST genes are up regulated in response to oxidative stress (Hayes & Pulford, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the understanding of the phenotype-genotype correlation is difficult due to modifying factors in thalassemia [ 2 ]. Several studies have been demonstrated that the occurring variation in some genes, such as HBA1, HBA2, HBB, HBG1, HBG2, BCL11A, COL1A1, CAT and GST genes can moderate the severity of thalassemia [ 16 , 17 , 18 , 19 , 20 ]. Recently, several studies have evaluated the effect of 3'-UTR SNPs on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the genes related to the severity of thalassemia intermedia (TI) were extracted from known literatures [ 16 , 17 , 18 , 19 , 20 ]and the mRNA expression profile and molecular functions of these genes were obtained. Then, miRNA target site SNPs were predicted by in silico analysis.…”
Section: Methodsmentioning
confidence: 99%